Pengembangan Game Edukasi Tebak Bendera Menggunakan Metode Game Development Life Cycle - Trifena Sweetly Kasenda; Reinal Eljre Moningka; Happyeaster Nathanael Maindoka; Abdon E. Sayori; Ade Yusupa; Brave A. Sugiarso; Yuri Akay; Kenneth Palilingan (Indo Publishing, 2025)
The development of information technology has encouraged the use of digital learning media that are more interactive and engaging, including educational games. This study aims to develop an educational game titled Guess the Flag as a learning medium for basic geography material for elementary school students. The development process follows the Game Development Life Cycle (GDLC), which consists of Initiation, Pre-Production, Production, Testing, Beta, and Release stages. The game was developed using Construct 3 and designed in the form of a multiple-choice quiz to help students recognize national flags interactively. The black-box testing results indicate that all game features function properly, including question display, answer options, answer validation, and scoring. User trials with students also show that the game is enjoyable, easy to use, and able to increase students’ interest in learning basic geography. Therefore, this educational game is considered feasible to be used as an interactive and effective learning medium.